2020
DOI: 10.3390/ani10050798
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Management Factors Affecting the Time Budgets of Free-Ranging Iberian Pigs Reared in Spain

Abstract: Understanding the natural behaviour of pigs in free-range conditions facilitates interpretation of their behaviour in intensive conditions. Studying six different farms over two years at different seasons, with climatic and management variations, allowed for a general description of Iberian pig behaviour and which factors have an influence on it. The main activity found was resting (56.5% of the time observed), followed by exploratory behaviour. However, this exploratory behaviour was higher when animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The ‘montanera’ finishing phase takes place from early November to late February, for pigs that are at least 10 months old and weighing between 80.5 and 115 kg (Rodríguez‐Estévez et al., 2010, 2011). In the traditional production system for the Iberian pig, both males and females are neutered to prevent boar taint after slaughter and also to avoid wild boar being attracted to the outdoor enclosure by entire females in heat (Martinez‐Macipe et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…The ‘montanera’ finishing phase takes place from early November to late February, for pigs that are at least 10 months old and weighing between 80.5 and 115 kg (Rodríguez‐Estévez et al., 2010, 2011). In the traditional production system for the Iberian pig, both males and females are neutered to prevent boar taint after slaughter and also to avoid wild boar being attracted to the outdoor enclosure by entire females in heat (Martinez‐Macipe et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…Sudden regrouping results in aggression and abnormal behavior of piglets (O'Connell et al, 2005 ; Grümpel et al, 2018 ). Intensive rearing improves economic efficiency, which affects the welfare status of piglets (Martinez-Macipe et al, 2020 ). In the recent years, researchers provided enriched social environments for piglets in lactation to improve their welfare (Salazar et al, 2018 ; Ko et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact of a reduced number of animals per group during the montanera could be explained because of the age of the animal, because more space was available or because they needed to be more focused on feeding strategies in forest areas and less on forming big groups in more open areas as in an anti-predator strategy (40). In fact, Martínez-Macipe et al (34) found a clear increase in exploratory/foraging behavior in Iberian pigs during montanera, in comparison to previous seasons where animals were fed, and in the present study, being in the montanera was positively correlated with being closer to trees and negatively with being closer to any other structure (fences, feeding area, drinker, water bath area and fences). Accordingly, Rodríguez-Estévez et al (1) determined that pigs grazing together accounted for four or fewer individuals, but when they were seen eating acorns there were only one or two animals together.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is just a minority of the animals being alone, as most of the pigs studied, males and females, formed into groups. Although the risk for predation is low for these Iberian pigs in the areas where they are reared, Martínez-Macipe et al ( 34 ) described in the same farms how animals at the periphery of the groups were more vigilant than were animals in the center, so some anti-predator instinct is maintained in these animals and, accordingly, a high percentage of gregariousness would be expected.…”
Section: Discussionmentioning
confidence: 99%